Hypothyroidism predicts worsened prognosis in patients undergoing percutaneous coronary intervention - Cohen, Ben; Bental, Tamir; Perl, Liat; Vaknin Assa, Hana; Codner, Pablo; Orvin, Katia; Barkan, Yeela Talmor; Levi, Amos; Kornowski, Ran; Perl, Leor (Frontiers in Cardiovascular Medicine, 2022)
Background: The link between thyroid dysfunction and cardiovascular disease is well established. Hypothyroidism has been significantly associated with increased risk of dyslipidemia, atherosclerosis and heart failure. However, little is known regarding its effect on patients undergoing percutaneous coronary intervention (PCI). Aim: The aim of study was to examine the impact of concomitant hypothyroidism on mortality and major adverse cardiac event (MACE) in patients undergoing PCI. Methods: The Rabin Medical Center PCI registry includes all consecutive patients who have undergone PCI between 2004 and 2020. We identified patients with prior diagnosis of hypothyroidism, and compared rates of mortality and MACE (comprising death, myocardial infarction, target vessel revascularization and/or coronary bypass surgery). Results: Among 28,274 patients, 1,922 (6.8%) were found to have hypothryoidism. These patients were older (70.3 ± 10.4 vs. 66.0 ± 11.8 y.o, P<0.001) and more likely to be women (34.2% vs. 26.1%, P<0.001). They had a higher prevalence of atrial fibrillation (10.8% vs. 7.7%, P<0.001), chronic renal dysfunction (25.1% vs. 18.7%, P=0.04) and dementia (2.9% vs. 1.8%, P=0.004). PCI was performed on ACS setting in 52-54% of patients in both groups (p=0.569). Unadjusted 5-year rates of all-cause mortality (26.9% vs. 20.3%, P<0.001) and MACE (40.3% vs. 29.4%, P<0.001) were higher for hypothyroid patients. A propensity match score was able to form 672 matched pairs of HT and control patients, showing similar results. Moreover, following multivariate analysis, TSH as a continuous parameter was associated with a higher risk of mortality and MACE (HR, 1.06 per additional 1 mIU/L; CI, 1.02–1.11; P<0.001 and HR, 1.07; CI, 1.02–1.12; P<0.001, respectively) at 5-year follow up. Conclusions: In our study, hypothyroidism confers worse outcomes in patients undergoing PCI. Further research is needed to establish effective ways to mitigate this augmented risk.